Vega: Low-Latency Zero-Knowledge Proofs over Existing Credentials - Kaviani, Darya; Setty, Srinath (2026)
As digital identity verification becomes increasingly pervasive, existing privacy-preserving approaches are still limited by complex circuit designs, large proof sizes, trusted setups, or high latency. We present Vega, a practical zero-knowledge proof system that proves statements about existing credentials without revealing anything else. Vega is simple, does not require a trusted setup, and is more efficient than the prior state-of-the-art: for a 1920-byte credential, Vega achieves 92 ms proving time, 23 ms verification time, 108 kB proofs, and a 464 kB proving key. For smaller credentials (896 bytes), these drop to 62 ms proving, 17 ms verification, and 83 kB proofs. At the heart of Vega are two principles that together enable a lightweight proof system that pays only for what it needs. First, fold-and-reuse proving exploits repetition and folding opportunities (i) across presentations, by pushing repeated work to a rerandomizable precomputation; (ii) across uniform hashing steps, by folding many steps into a single step; and (iii) for zero-knowledge, by folding the public-coin transcript with a random one. Second, lookup-centric arithmetization extracts relevant values from credential bytes, both for extracting relevant fields without full in-circuit parsing, and to enable length-hiding hashing.